Predictive factors for visual prognosis in neurosyphilis presenting with optic atrophy: a Chinese case series study - Zhu, Mingjie; Gu, Xin; Zhou, Pingyu; Yan, Yan (Frontiers in Neurology, 2025)
BackgroundWe aimed to explore the clinical features and predictive factors for visual prognosis of neurosyphilis-associated optic atrophy (NSAOA).MethodsThis retrospective observational study included 17 patients (33 eyes) with NSAOA who received standard anti-ocular syphilis treatment. LogMAR (logarithm of the minimum angle of resolution) best-corrected visual acuity (BCVA), visual field, and optical coherence tomography, were recorded at baseline, short-term (within one month after treatment), and long-term (> 6 months) follow-up. Patients with at least one eye with LogMAR BCVA of ≥1.3 at the last follow-up visit were categorized as the blind group. A change ≥0.2 on the LogMAR BCVA indicated improvement or deterioration.ResultsThe mean age was 58.5 years, and 15 patients were males. The mean time between the onset and treatment was 10.1 months. Thirteen patients had Argyll-Robertson pupils. The unblinded group had younger age, shorter disease duration, better baseline visual acuity, higher baseline cerebrospinal fluid (CSF) venereal disease research laboratory (VDRL) titer and CSF total protein counts than the blind group. BCVA of most eyes improved after treatment but experienced deterioration during the follow-up. The deteriorated group of eyes had lower baseline visual field parameters, thinner inferior peripapillary retinal nerve fiber layer (RNFL) thickness. The long-term LogMAR BCVA moderately negatively correlated with CSF VDRL titers before and after treatment.ConclusionThe diagnosis is often delayed in NSAOA, and the overall visual prognosis is poor. Older age, longer symptom duration, worse baseline vision, thinner RNFL thickness, and lower CSF VDRL titer and total protein counts are significantly associated with worse long-term visual prognosis. The correlation between syphilis serologic test and visual prognosis is poor. It is recommended to reexamine CSF in the follow-up.